1996
DOI: 10.1002/(sici)1096-9071(199608)49:4<274::aid-jmv3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

HLA DRB1 and DQB1 alleles and haplotypes influencing the progression of hepatitis C

Abstract: Some HLA class II alleles and haplotypes were examined by restriction fragment length polymorphism of corresponding DNA fragments amplified by the polymerase chain reaction in 117 patients with chronic hepatitis C in Japan. The prevalence rates were compared between patients and 1216 controls and in 67 patients with liver cirrhosis, of whom 20 had hepatocellular carcinoma and 50 patients with chronic hepatitis who did not have cirrhosis or hepatocellular carcinoma. Notably, DRB1*0405 (49% [95% confidence range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 21 publications
(16 reference statements)
1
38
1
1
Order By: Relevance
“…Two Japanese studies compared HCV carriers with normal liver function tests and normal histology with patients with elevated liver function tests and cirrhosis, respectively. 61,62 In both studies, DQB1*0401, DRB1*0405, and the two-locus haplotype consisting of these alleles were more frequent in those who developed chronic liver disease. However, because Kuzushita et al also typed class I alleles, they showed that subjects with the three-locus haplotype, HLA-B54-DQB1*0401-DRB1*0405, were 13 times as likely to have liver injury relative to those with the two-locus haplotype without B54.…”
Section: Hepatitis C Virusmentioning
confidence: 84%
“…Two Japanese studies compared HCV carriers with normal liver function tests and normal histology with patients with elevated liver function tests and cirrhosis, respectively. 61,62 In both studies, DQB1*0401, DRB1*0405, and the two-locus haplotype consisting of these alleles were more frequent in those who developed chronic liver disease. However, because Kuzushita et al also typed class I alleles, they showed that subjects with the three-locus haplotype, HLA-B54-DQB1*0401-DRB1*0405, were 13 times as likely to have liver injury relative to those with the two-locus haplotype without B54.…”
Section: Hepatitis C Virusmentioning
confidence: 84%
“…In infants born to infected mothers HLA DRB1*1104 is associated with seroreversion and DRB1*1101 with viral persistence [79] for HCV infection. In Japanese and the DRB1*0901-DQB1*0303 haplotype is related to protection from cirrhosis in hepatitis C [70] and HLA B44-DRB1*1302-DQB1*0604 and DRB1*1302-DRB1*0604 with asymptomatic carrier phenotype [68] . HLA class Ⅲ allele associations: HLA class Ⅲ and cytokine genes have been reported in influencing HCV infection outcome.…”
Section: Viral Persistence and Viral Clearancementioning
confidence: 99%
“…Increased expression of inhibitory receptor CD94/NKG2A on NK cells was found in chronic hepatitis C patients and is suggested to contribute to immune resistance towards HCV infection and HCV mediated cellular transformation via modulating dendritic cell function and cytokine secretion [66,67] . HLA class Ⅱ allele associations: HLA DRB1*0405 and DQB1*0401/0402 alleles are associated with viral persistence and chronic HCV infection in Japanese [68][69][70] . Also, DRB1*0405-DQB1*0401/0402 haplotype [59] and HLA B54-DRB1*0405-DQB1*0401 haplotype are associated with HCV induced liver injury [68] .…”
Section: Viral Persistence and Viral Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] In contrast, several studies have suggested that specific HLA class II alleles may influence outcome parameters in chronic HCV infection such as disease susceptibility, viral clearance, or disease severity. [15][16][17][18][19][20][21] However, many of these studies were small and reported inconsistent findings. Despite the propensity of HCV to present a diverse range of epitopes for T cell recognition, heterozygous advantage has not been addressed or demonstrated in these studies.…”
mentioning
confidence: 99%